Exploration of PVC@SiO2 nanostructure for adsorption of methylene blue via using quartz crystal microbalance technology - Safaa S. Ali; Gamal K. Hassan; Sameh H. Ismail; A. A. Ebnalwaled; Gehad G. Mohamed; M. Hafez (Scientific Reports, 2023)
Abstract Methylene blue (MB) dye is considered a well-known dye in many industries and the low concentration of MB is considered very polluted for all environment if it discharged without any treatment. For that reason, many researchers used advanced technologies for removing MB such as the electrochemical methods that considered very simple and give rapid response. Considering these aspects, a novel quartz crystal microbalance nanosensors based on different concentrations of PVC@SiO2 were designed for real-time adsorption of MB dye in the aqueous streams at different pHs and different temperatures. The characterization results of PVC@SiO2 showed that the PVC@SiO2 have synthesized in spherical shape. The performance of the designed QCM-Based PVC@SiO2 nanosensors were examined by the QCM technique. The sensitivity of designed nanosensors was evaluated at constant concentration of MB (10 mg/L) at different pHs (2, 7 and 11) and temperatures (20 °C, 25 °C, and 30 °C). From the experimental, the best concentration of PVC@SiO2 was 3% for adsorbed 9.99 mg of cationic methylene blue at pH 11 and temperature 20 °C in only 5.6 min.